Magnetic‐Field Tunable Intertwined Checkerboard Charge Order and Nematicity in the Surface Layer of Sr2RuO4 (Adv. Mater. 32/2021). Issue 32 (12th August 2021) - Marques, Carolina A.; Rhodes, Luke C.; Fittipaldi, Rosalba; Granata, Veronica; Yim, Chi Ming; Buzio, Renato; Gerbi, Andrea; Vecchione, Antonio; Rost, Andreas W.; Wahl, Peter
Abstract : Sr2 RuO4 Surface Layers As reported by Peter Wahl and co‐workers in article number 2100593, small structural distortions in the surface layer of Sr2 RuO4 create a system with radically different properties compared to the bulk, giving rise to multiple van Hove singularities and nematic and checkerboard charge orders. The image shows the structure of the van Hove singularity in reflection from the checkerboard order and nematicity, which are both required to understand the new exciting physics.